Thesis which means “That New Generation of Sociologists Matured in the Independent Lithuania, has Entered the Academic Stage” - Gedutis, Aldis (Problemos, 2002)
Liutauro Kraniausko disertacijos „Sociologinio diskurso raida Lietuvoje (1960-2000 m.)“ recenzija